The asymmetry of franchising, multi-level marketing and pyramid schemes - Mohd Ishan, Zahira (McGraw-Hill Education (Malaysia) Sdn. Bhd., 2013)
This chapter discusses how consumers who are looking to start a business usually get confused between the legal and illegal way of doing it. Franchise shares many common characteristics with multi-level marketing and pyramid schemes. This chapter discusses the nature of the three forms of doing business.